2003
DOI: 10.1097/00008877-200312000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 5-HT2 receptor agonist, DOI (2,5-dimethoxy-4-iodoamphetamine), and antagonist, ketanserin, on the performance of rats on a free-operant timing schedule

Abstract: This experiment examined the effect of a 5-HT2 receptor agonist DOI (2,5-dimethoxy-4-iodoamphetamine), and antagonist, ketanserin, on temporal differentiation performance. Twelve rats were trained under the free-operant psychophysical procedure to press two levers (A and B) in 50-s trials in which sucrose reinforcement (0.6 mol/l, 50 microl) was provided intermittently for responding on A during the first half, and on B during the second half of the trial. Psychometric curves were derived from percent respondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
33
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 25 publications
20
33
1
Order By: Relevance
“…They also suggest the possibility that stimulus control is relatively weak and may be more vulnerable to disruption at longer stimulus durations. These results are similar to those of Body et al (2003), who found that DOI also altered temporal differentiation in the freeoperant psychophysical procedure in rats, an effect that was similarly blocked by ketanserin. Asgari et al (2006b) examined the effect of (2)-DOI (0.25 mg/kg, s.c.) on the fixed-interval peak procedure in 18 female rats.…”
Section: Effects On Time Perceptionsupporting
confidence: 90%
“…They also suggest the possibility that stimulus control is relatively weak and may be more vulnerable to disruption at longer stimulus durations. These results are similar to those of Body et al (2003), who found that DOI also altered temporal differentiation in the freeoperant psychophysical procedure in rats, an effect that was similarly blocked by ketanserin. Asgari et al (2006b) examined the effect of (2)-DOI (0.25 mg/kg, s.c.) on the fixed-interval peak procedure in 18 female rats.…”
Section: Effects On Time Perceptionsupporting
confidence: 90%
“…In agreement with previous findings using Stubbs' freeoperant psychophysical procedure (Stubbs 1976;White 1994a, b, 1997;Chiang et al 1998Chiang et al , 1999Chiang et al , 2000aMachado and Guilhardi 2000;Body et al 2002Body et al , 2003Body et al , 2004Body et al , 2006aCheung et al 2006), response rate on lever A declined, while response rate on lever B increased, as a function of time from trial onset, this being reflected in an increasing percentage of total responding being devoted to lever B (%B) as the trial progressed. The absolute rate of responding on lever B tended to decline towards the end of the trial.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, SKF-81297 (0.2 and 0.4 mg kg −1 ) reduced overall response rate without affecting T 50 , indicating that a change in T 50 was not an inevitable consequence of a reduction of response rate. Finally, previous experiments on the effects of drugs acting at 5-hydroxytryptamine 5-HT receptors have demonstrated dissociation of effects of drugs on response rate and T 50 (Body et al 2003(Body et al , 2004.…”
Section: Discussionmentioning
confidence: 81%
“…The antagonism tests with ketanserin demonstrated that it could reverse the attenuation of the nicotine stimulus produced by DOI. Ketanserin is a 5-HT antagonist that acts at the 5-HT 2A receptor (Body et al 2003), although it may also have activity at the 5-HT 2C receptor (Glennon et al 2002). The ketanserin results suggest that the 5-HT 2A receptor subtype is playing an important role in the attenuation of the discriminative stimulus effects of nicotine by DOI, although at this time it is unclear exactly what this role is.…”
Section: Discussionmentioning
confidence: 99%